Phubbing dan Permasalahan Sosial dalam Perkembangan Teknologi Informasi di Kalangan Siswa Generasi Z - Yose Putri, Kanaya; Firman, Firman; Netrawati, Netrawati (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
Phubbing is a term to describe the behavior of someone who focuses on their smartphone when interacting with other people, thereby avoiding direct communication. This study aims to describe the development of technology and phubbing along with the social problems that arise among generation Z students. This research uses a qualitative approach to describe the actual situation of the phenomenon under study so that objective data is obtained. Data collection methods are observation and interviews. The research results show that phubbing behavior among students is characterized by dependence on smartphones, ignoring social interactions, and preferring digital activities to direct communication with friends. Apart from that, social problems that arise include reduced opportunities for interaction, increased tendencies to be alone, social death, an attitude of not caring about the environment, and a change in role from phubee to phubber. So it can be concluded that technological developments have also triggered the emergence of phubbing behavior and various social problems.